Insomnia and the menopause: Where are we and where are we going? (Research, Society and Development, 2024)
The menopause, marked by a decrease in ovarian follicles and changes in female sex hormones, can trigger symptoms such as facial flushing and sleep disturbances. Hormonal fluctuations, notably a decrease in estrogen and progesterone, are associated with night-time awakenings and difficulty maintaining uninterrupted sleep. This condition has a negative impact on quality of life, leading to conditions such as obesity, diabetes, cardiovascular disease, and depression. The transition to menopause intensifies sleep disorders, especially insomnia, which is often associated with hot flashes. Despite the lack of clear evidence on the efficacy of hormone therapy, its use persists, highlighting the need for personalized approaches. Therapeutic strategies, such as the fusion of hormone therapy with sleep hygiene and cognitive-behavioral therapy, are emerging as promising. Some recommendations include adjustments to sleep habits, regular exercise, and a balanced diet. In conclusion, menopause significantly influences sleep disorders in women, affecting various aspects of physical and emotional health. Comprehensive therapeutic strategies, including behavioral changes, hormone therapy, and nutritional support, show promise for improving quality of life during this inevitable transition in female aging.